Female advantage in neoadjuvant pancreatic cancer therapy: is it down to macrophages? - Michl, Patrick; Roth, Laura (Gut, 2023)
Pancreatic cancer still carries the worst survival rate among all solid tumours, mostly due to the absence of early symptoms and a lack of satisfying treatment options, leading to an appalling 5-year survival rate of less than 12%. The only potentially curative treatment option is surgical resection followed by adjuvant chemotherapy. Since pancreatic cancer is usually diagnosed at advanced stage, treatment with curative intent can be provided to only 15-20% of patients. However, even after surgical resection, most patients develop local or systemic recurrence. During recent years, neoadjuvant chemotherapeutic regimens have been introduced for locally advanced or borderline resectable cancers to improve the chances for secondary resection (eg, CONKO007,1 PREOPANC,2 NEOLAP3). However, even after this sequential approach, only for a minority of patients long-term survival can be achieved. In the resectable situation, the role of neoadjuvant therapy remains to be determined, with conflicting results of the few available trials (eg, NEONAX4). - - It is likely that subgroups of patients benefit from neoadjuvant approaches that are yet to be molecularly characterised. Optimising neoadjuvant systemic therapies by identifying these molecular subgroups of patients with clinical benefit from this approach is highly desirable …
Online veröffentlicht: 9. Oktober 2023
Gesehen am 03.01.2024